2020
DOI: 10.1080/22221751.2020.1830717
|View full text |Cite
|
Sign up to set email alerts
|

Rapid humoral immune responses are required for recovery from haemorrhagic fever with renal syndrome patients

Abstract: Haemorrhagic fever with renal syndrome (HFRS) following Hantaan virus (HTNV) infection displays variable clinical signs. Humoral responses elicited during HTNV infections are considered important, however, this process remains poorly understood. Herein, we have investigated the phenotype, temporal dynamics, and characteristics of B-cell receptor (BCR) repertoire in an HFRS cohort. The serological profiles were characterized by a lowered expression level of nucleoprotein (NP)-specific antibody in severe cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…At the very beginning of the acute phase, IgM and IgG antibodies can be detected that react with hantaviral NP [ 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 ] while antibodies against Gc and Gn appear later during the progress of disease [ 212 ]. Furthermore, the serological profile following Hantaan virus infection (hemorrhagic fever with renal syndrome (HFRS)) inversely correlates with the level of NP-specific Abs and illness severity [ 213 ].…”
Section: Immunity To Npmentioning
confidence: 99%
“…At the very beginning of the acute phase, IgM and IgG antibodies can be detected that react with hantaviral NP [ 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 ] while antibodies against Gc and Gn appear later during the progress of disease [ 212 ]. Furthermore, the serological profile following Hantaan virus infection (hemorrhagic fever with renal syndrome (HFRS)) inversely correlates with the level of NP-specific Abs and illness severity [ 213 ].…”
Section: Immunity To Npmentioning
confidence: 99%
“…We began by collecting the relevant fastq les for human-derived samples infected with Orthohantavirus strains. In total, we included 73 samples from six datasets in this meta-analysis, including 23 controls, and included all pertinent data and metadata that could be extracted from the NCBI-GEO and ENA databases [11][12][13][14]. Fastq les were divided into in vitro and in vivo groups for the analysis according to sample type and each group was separately input to ARMOR.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these same terms were used to nd relevant datasets within the European Nucleotide Archive (ENA) database. The corresponding RNA-sequencing data for ve GEO series were retrieved from the Sequence Read Archive (SRA; https://www.ncbi.nlm.nih.gov/sra) at NCBI: GSE158712, GSE161354, GSE133319, GSE133634, GSE133751 [11][12][13]. Sequencing data with the experiment accession number PRJEB41624 was also downloaded from ENA and used in this analysis [14].…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Among the most vital signaling pathways altered early by hantaviruses are cytokine-cytokine receptor interactions, chemokine signaling, STAT signaling, MAPK signaling, and neurotrophic factor signaling, and there is a significant increase in antigen processing and presentation pathways, as well as the cytotoxicity of NK cells ( 41 ). Previous investigation has suggested that the rate of revitalization and alteration of memory B cells is significantly accelerated in moderate cases of HFRS patients compared to severe cases; thus, the rapid expansion of HTNV-specific B cells in the early stages of infection is closely connected to the disease outcome ( 42 ). It is likely that IL-2Ralpha, MIG, IFNalpha2, SCF, and PDGFBB are involved in the activation of the immune pathways and immune cells mentioned above.…”
Section: Discussionmentioning
confidence: 99%